Comparison of complete IV antibiotic course versus partial IV with oral antibiotics in probable and proven early-onset sepsis in a tertiary care centre; a step toward antimicrobial stewardship in the neonatal intensive care unit: a prospective observational study - Khan, Sana; Singh, Abhishek; Gupta, Navratan; Chauhan, Ravi S. (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal sepsis, particularly early onset sepsis (EOS), remains a leading cause of neonatal morbidity and mortality. The standard treatment involves intravenous (IV) antibiotics; however, prolonged IV antibiotic use increases hospital stay, healthcare costs, and the risk of antimicrobial resistance. Transitioning from IV to oral antibiotics in stable neonates may be a viable alternative. Aim and objectives were to compare the clinical outcomes of neonates with EOS receiving a complete course of IV antibiotics versus those transitioning from IV to oral antibiotics following initial stabilization. Methods: A prospective observational study was conducted at the neonatal intensive care unit (NICU) of L.L.R.M Medical College, Meerut, from April 2023 to April 2024. Neonates diagnosed with EOS were categorized into two groups: group A (complete IV antibiotic course) and group B (IV-to-oral transition). Data on neonatal demographics, clinical parameters, duration of hospital stay, readmission rates, mortality, and weight gain were analysed. Statistical comparisons were performed using Chi-square and independent t-tests, with a p value <0.05 considered significant. Results: A total of 100 neonates were included (50 per group). The mean hospital stay was significantly shorter in group B (7.2±1.4 days) compared to group A (10.1±2.1 days; p<0.01). No significant difference in mortality was observed between the groups (group A: 4%, group B: 3%; p=0.68). Readmission rates were comparable (group A: 6%, group B: 5%; p=0.74). Weight gain was significantly higher in group B at follow-up (p=0.03). The incidence of hospital-acquired infections was lower in group B, suggesting potential benefits of early transition to oral therapy. Conclusions: Early transition from IV to oral antibiotics in stable neonates with EOS is a safe and effective strategy that reduces hospital stay without increasing mortality or readmission rates. This approach may contribute to antimicrobial stewardship by minimizing unnecessary IV antibiotic exposure. Further large-scale studies are needed to establish standardized protocols.